Research on the application of improved NSGA-II in the structure design of wind turbine blade spar cap - Chen, Cheng; Wang, Long; Niu, Muhua (Frontiers in Energy Research, 2023)
The blade is one of the most important parts of a wind turbine. Blade design is a complicated process involving many design links and mutual couplings. To efficiently obtain the Pareto Front and optimal blade, a novel methodology combined the improved NSGA-II with Thin-Walled Beam Theory and Classic Laminated Theory has been developed. In the optimization study, the design parameters are the thickness distribution of the spar cap and a parametric model based on blade production process is developed. The objective function is on the minimization of mass and the maximization of flapwise stiffness. As a practical engineering application research, a 15MW wind turbine IEA-15-240-RWT developed by NREL is used as a reference model. Laws on the number of variables, blade profiles, design loads and natural frequencies present in the design have been studied through Pareto fronts obtained from multi-objective optimization results, and these laws have important implications for practical engineering design work. Meanwhile, the results show that the new methodology is effective for blade structure design, and that this approach can be easily extended to study the design of influence laws for more design parameters or more complex blade design problems.